THE NATSIR INTEGRAL MOTION IN GEOPOLITICAL PERSPECTIVE - Fauzan, Pepen Irpan; Fata, Ahmad Khoirul; Ananda, Rifki Abror (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The peaceful transformation of the Republic of the United States of Indonesia (RIS) into the Unitary State of the Republic of Indonesia (NKRI) represents a defining milestone in the nation’s post-independence trajectory. This study examines the pivotal role of Mohammad Natsir, a leading Islamic intellectual and statesman, who initiated the Integral Motion that catalyzed Indonesia’s reunification. Through historical and socio-political analysis, this research explores the political strategies, diplomatic negotiations, and moral convictions that shaped Natsir’s leadership during this critical period. Utilizing a qualitative methodology rooted in the social scientific history paradigm, the study combines historical inquiry with structuralist theory to analyze both the internal fragmentation and external pressures that Indonesia faced in the early years of its independence. The findings reveal Natsir's instrumental role not only as a political leader but also as a key architect of national integration. His ability to mediate between federalist and unitarian forces, while maintaining a vision grounded in moral and ideological commitment, proved crucial in resolving divisive tensions. By fostering consensus among RIS constituent states, Natsir’s initiative laid the groundwork for a unified Indonesian state, steering the nation toward political consolidation and stability. This research contributes to a deeper understanding of Indonesia’s early state-building efforts and underscores the urgent need to revisit and recognize the foundational roles of key national figures in shaping modern Indonesia. In an era of renewed interest in national identity and cohesion, Natsir's legacy offers valuable insights into leadership, diplomacy, and the pursuit of unity through peaceful means.